Análise do treinamento muscular do assoalho pélvico na função perineal e satisfação sexual em mulheres no pós-parto vaginal - Benetti, Isadora (2022)
Introduction: Pregnancy and childbirth, in addition to being an important period in a woman's life, undergo several physical and hormonal changes that cause marked effects on mothers' health and their quality of life. Objective: This research aims to analyze the effect of pelvic floor muscle training (PFMT) on perineal function and sexual satisfaction in women after vaginal delivery. Methods: This research consists of an open clinical trial carried out at the Puerperium Outpatient Clinic of the University Hospital of Santa Maria, from August 2020 to December 2021. Women aged 18 years or older were included in the study; who have performed vaginal delivery without laceration or with grade I and II laceration; primiparous or who have 2 to 3 previous deliveries and voluntarily agreed to participate in the research. Participants were followed up for two and a half months and divided into two groups: intervention (GI) and control (GC). All patients included in the study underwent a detailed anamnesis, the application of the Pelvic Floor Impact Questionnaire (PFIQ-7) and Female Sexual Function Index (FSFI) answered in meetings 1 and 3, finally, the assessment of floor muscle strength pelvic exam performed in consultations 1, 2 and 3. A PFMT program was designed with perineal strengthening exercises, which only the GI participants performed. Results: 124 postpartum women were consecutively invited to participate in the study. Of these, 46 were excluded for not returning to the outpatient clinic. The study sample consisted of 78 participants divided into two groups: GI (n=38) and GC (n=40). The results obtained in this study are organized in the form of two scientific articles. The first showed, in GI, a decrease in the symptoms of urinary loss in the participants regarding the gestational period, in addition to an increase in PFM strength in the postpartum period.The second article revealed that, as time went by, PFM strength and female sexual satisfaction, assessed by the FSFI instrument, improved for these women through pelvic floor strengthening exercises, compared to the CG, which worsened in the FSFI domains, in addition to showed no relationship with pelvic floor muscle strength.Conclusion: Pelvic floor muscle training has clearly shown its relevance in the postpartum period. Because it is an effective, non-invasive and lowcost method, it proved to be an important tool in the faster recovery of the female organism in the puerperium, improving PFM strength, sexual satisfaction, reducing urinary incontinence in this woman's life.